TRANSFERIBILIDADE DE MARCADORES SSR DE TOMATE PARA SOLANÍCEAS NATIVAS DA MATA ATLÂNTICA E VARIABILIDADE GENÉTICA EM Solanum mauritianum Scop. UTILIZANDO MARCADORES ISSR - Lima, Daniele Luciana de (2015)
The biological diversity of the Atlantic Forest is under constant pressure, being mainly affected by human actions. These actions have resulted in the fragmentation of this biome. In disturbed and open areas pioneer plants species play an important role in their recovery. The solanaceous family has several pioneer species. In this study, in order to investigate the genetic diversity of natural populations, 72 EST-SSR (expressed sequence tag - simple sequence repeat) primers pairs developed in tomato, were evaluated in seven Solanaceae species native of the Atlantic Forest and 10 ISSR primers (inter-simple sequence repeat) were run in two Solanum mauritianum Scop. populations. To test the transferability of EST-SSR primers were used the DNA of five plants of each species. To evaluate the potential of ISSR markers in genetic studies in S. mauritianum 10 ISSR primers were run in two populations of the species. The population "A" was collected in Guarapuava, PR, near a conservation area and the "B" population was collected in Pitanga, PR, in an agricultural area. Of 72 EST-SSR primer pairs tested on seven species, 55 showed amplification products with different percentages of amplification on different species: 48.6% in Solanum mauritianum Scop., 33.3% in Solanum americanum Mill., 36.5% in Solanum guaraniticum A. St.-Hil., 33.3% in Solanum hasslerianum Chodat, 29.2% in Solanum viarum Dunal, 18.1% in Solanum sisymbriifolium Lam. and 22.2% in Brugmansia suaveolens (Humb. & Bonpl. ex Willd.) Bercht. & J. Presl. The data obtained show that there is moderate transferability rate of the SSR primer from coding regions of tomatoes to the solanaceous species evaluated. The highest polymorphism was observed in SSR primers that amplified fragments in S. guaraniticum (60.9%) in contrast to what was found in S. sisymbriifolium (16.6%). The polymorphism found was the presence of null alleles which prevents the use of EST-SSR primers for population genetic studies in the evaluated species. In the study using ISSR primers in S. mauritianum, the percentage of polymorphism was 87.6% and 80.30% for the population "A" and "B" respectively. The population "A" had 5 unique loci while the "B", only 1. A grouping of all individuals formed 10 groups, showing weak structure in thepopulations studied. The molecular variance analysis showed a high rate of gene flow (10.78). Genetic variation within populations was greater (93.5%) than between them (6.49%), the variation found between populations was low (GST = 0.044). High genetic diversity was observed by Shannon index (A = 0.53, B = 0.46) and between populations (0.52). The data obtained from the ISSR markers showed that even more than 100 km away the populations have high gene flow. This behavior can be explained by the biological characteristics of the species and associations that the plant establishes with animals. The results from our study show that the SSR markers developed for tomato are not useful for genetic studies in native Solanaceae, while the ISSR markers were very effective to obtain population genetic data from S. mauritianum populations.